2022
DOI: 10.1080/01443615.2022.2114332
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and associated factors of low birth weight among term newborns delivered in Addis Ababa public hospitals, Ethiopia, 2021

Abstract: Background: Low birth weight (LBW) accounts for 60% to 80% of all neonatal deaths each year. In developing countries like Ethiopia, low birth weight is a major public health concern. Almost half of the world's infants are not weighed at birth, a gure that is especially high in Sub-Saharan Africa including Ethiopia. Only 14% of births had information on birth weight were available at the time of birth in Ethiopia. So previous studies underestimate the magnitude and associated factors of low birth weight. As a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
2
1
0
Order By: Relevance
“…The prevalence (15.8%) of LBW in the current study is comparable to the prevalence of LBW reported for Eastern Sudan (15.3%; Adam et al, 2008) and Darfur, Western Sudan (14.9%; Haggaz et al, 2010). However, the prevalence was slightly higher than that reported for Khartoum, Sudan (12.1%; Bilal et al, 2022), Wad Medani (Central Sudan: 12.6%; Elhassan et al, 2010), Addis Ababa, Ethiopia (13.06%; Tadesse et al, 2023), Ghana (13.5%; Ahenkorah et al, 2022), and Tanzania (21%; Kamala et al, 2018). A pooled prevalence of 5.7% for LBW was recently reported in the Demographic and Health Survey of Saharan African countries, which enrolled 33,585 newborns (Weyori et al, 2022).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The prevalence (15.8%) of LBW in the current study is comparable to the prevalence of LBW reported for Eastern Sudan (15.3%; Adam et al, 2008) and Darfur, Western Sudan (14.9%; Haggaz et al, 2010). However, the prevalence was slightly higher than that reported for Khartoum, Sudan (12.1%; Bilal et al, 2022), Wad Medani (Central Sudan: 12.6%; Elhassan et al, 2010), Addis Ababa, Ethiopia (13.06%; Tadesse et al, 2023), Ghana (13.5%; Ahenkorah et al, 2022), and Tanzania (21%; Kamala et al, 2018). A pooled prevalence of 5.7% for LBW was recently reported in the Demographic and Health Survey of Saharan African countries, which enrolled 33,585 newborns (Weyori et al, 2022).…”
Section: Discussionsupporting
confidence: 71%
“…Another notable finding of the current study was that maternal anemia increased the risk of LBW by 4.7 times. Several studies have also reported similar findings for other regions of Sudan and Africa—Wad Mani in Central Sudan ( Elhassan et al, 2010 ), Kassala in Eastern Sudan ( Ali et al, 2011 ), Darfur in Western Sudan ( Haggaz et al, 2010 ), Ethiopia ( Deriba and Jemal, 2021 ; Tadesse et al, 2023 ), Somalia ( Barut and Mohamud, 2023 ), Sierra Leone ( Kargbo et al, 2021 ), Uganda ( Odongkara et al, 2022 ), and Ghana ( Mohammed et al, 2019 ). This association was further corroborated by several meta-analyses that have shown that anemic pregnant women are at a higher risk of delivering newborns with LBW ( Rahman et al, 2016 ; Young et al, 2019 , 2023 ).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation